Between the judiciary and advocacy: professional preferences of law students in Serbia - Đorđević, Mila (Sociološki pregled, 2022)
In this paper, the author will present the issue of professional preferences of law students, with a special emphasis on the preferences towards the judiciary and the advocacy as professions. The first part of the paper presents the most important legal professions in Serbia, while the second part of the text presents the results of quantitative research conducted at the Faculty of Law, the University of Belgrade. In the concluding discussion, the author will try to systematize the obtained results and give an explanation for them by presenting the motives that students are guided by when choosing a future profession and by comparing working conditions in the judicial and attorney professions.